Niemann-Pick type C disease: The atypical sphingolipidosis. (December 2018) - Newton, Jason; Milstien, Sheldon; Spiegel, Sarah
Abstract: Niemann-Pick type C (NPC) disease is a lysosomal storage disorder resulting from mutations in either the NPC1 (95%) or NPC2 (5%) genes. NPC typically presents in childhood with visceral lipid accumulation and complex progressive neurodegeneration characterized by cerebellar ataxia, dysphagia, and dementia, resulting in a shortened lifespan. While cholesterol is widely acknowledged as the principal storage lipid in NPC, multiple species of sphingolipids accumulate as well. This accumulation of sphingolipids led to the initial assumption that NPC disease was caused by a deficiency in a sphingolipid catabolism enzyme, similar to sphingomyelinase deficiencies with which it shares a family name. It took about half a century to determine that NPC was in fact caused by a cholesterol trafficking defect, and still as we approach a century after the initial identification of the disease, the mechanisms by which sphingolipids accumulate remain poorly understood. Here we focus on the defects of sphingolipid catabolism in the endolysosomal compartment and how they contribute to the biology and pathology observed in NPC disease. This review highlights the need for further work on understanding and possibly developing treatments to correct the accumulation of sphingolipids in addition to cholesterol in this currently untreatable disease.